2018
DOI: 10.1038/s41525-018-0052-9
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating epilepsy genetics into clinical practice: a 360°evaluation

Abstract: We evaluated a new epilepsy genetic diagnostic and counseling service covering a UK population of 3.5 million. We calculated diagnostic yield, estimated clinical impact, and surveyed referring clinicians and families. We costed alternative investigational pathways for neonatal onset epilepsy. Patients with epilepsy of unknown aetiology onset < 2 years; treatment resistant epilepsy; or familial epilepsy were referred for counseling and testing. We developed NGS panels, performing clinical interpretation with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 48 publications
(49 reference statements)
0
39
0
Order By: Relevance
“…However, it has also been seen in a patient with drug‐resistant focal epilepsy and mild ID . In contrast to the mild SCN8A ‐related epilepsies associated with Gly1483Lys and Asn1877Ser, the Ile1327Val variant has been reported in four unrelated patients with a devastating neonatal or even intrauterine onset DEE associated with severe to profound ID, hypotonia, and movement disorder …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has also been seen in a patient with drug‐resistant focal epilepsy and mild ID . In contrast to the mild SCN8A ‐related epilepsies associated with Gly1483Lys and Asn1877Ser, the Ile1327Val variant has been reported in four unrelated patients with a devastating neonatal or even intrauterine onset DEE associated with severe to profound ID, hypotonia, and movement disorder …”
Section: Resultsmentioning
confidence: 99%
“…Pathogenic variants in SCN8A have originally been described in patients with developmental and epileptic encephalopathy (DEE), accounting for approximately 1% of DEEs . The number of SCN8A ‐related phenotypes is rapidly increasing, with the inclusion of SCN8A in gene panels and the expanded use of whole exome sequencing for diagnostic assessment of patients with epilepsy syndromes . Recently, it became obvious that SCN8A could cause more benign forms of epilepsy with normal cognition and treatable seizures .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic Characteristics In Drug-resistant Epilepsy Of Published Studies Table 3 provides a summary of previous studies about genetic characteristics in DRE [12][13][14][15][16][17][18][19][20][21]. Regardless of varied molecular diagnostic tool used between studies, some gene mutations were found to appear repeatedly, such as SCN1A (5.6%, n = 74/1308), followed by SCN8A (1.37%, n = 18/1308), TSC2 (1.22%, n = 16/1308), SCN2A (1.07%, n = 14/1308) and KCNQ2 (0.99%, n = 13/1308) 3).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic insights have been particularly transformative in our understanding of some of the most severe disorders of neurodevelopment, known now as developmental and epileptic encephalopathies (DEEs) (Scheffer et al, 2016). DEEs usually occur as isolated cases in families, yet in a large proportion of cases, causative de novo mutations in single genes can now be identified from clinical genetic diagnostics (Epi et al, 2013;Oates et al, 2018). The most common genes and their functional effects are illustrated in Figure 1.…”
Section: Severe De Novo Mutations and Genomic Alterations In Neurodevmentioning
confidence: 99%